Palaeoceanography of Lower Cretaceous Alpine platform carbonates. Issue 1 (7th January 2013) - FÖllmi, Karl B.; Godet, Alexis; Weissert, Helmut
Abstract Shallow‐water carbonate platforms evolve in an interplay of local, regional and global dynamics, thereby generating a detailed record of environmental conditions. Platform sediments constitute important archives of past environmental change and, as such, they are increasingly analysed for the information they contain on wider‐scale patterns. The integration of this information with palaeoceanographic data obtained from deeper‐water sediments provides a powerful tool to develop a more diverse and complete image of past environmental change. In this contribution, the remains of the northern Tethyan carbonate platform of Early Cretaceous age cropping out in the western Swiss Jura and the Helvetic Alps are used to illustrate the advantage of a palaeoceanographic approach in their interpretation. The tools applied are biostratigraphy and chemostratigraphy (carbon and strontium isotopes) in order to obtain a precise age model for correlation with (hemi‐)pelagic sediments in adjacent basins, sequence stratigraphy as a means to reconstruct the impact of sea‐level change, phosphorus stratigraphy as a proxy for trophic levels, facies and microfacies analyses as a gateway to gain better insight into the carbonate factory, and the detailed analysis of platform‐drowning unconformities as an indicator of wider‐scale palaeoenvironmental change. It is shown that changes from periods of predominantly photozoan to predominantly heterozoan carbonate production near the Berriasian–Valanginian boundary and middle early Aptian coincided with substantial increases in phosphorus burial rates and major carbon‐isotope excursions. Furthermore, the majority of the platform‐drowning episodes occurred just prior to and during episodes of major palaeoenvironmental change and, last but not least, the platform itself may have influenced the chemistry of adjacent basins and the carbon‐isotope composition of associated carbonates by the export of periplatform ooze.